A new genus and thirteen new species of sea stars (Asteroidea: Echinasteridae) from the Aleutian Island Archipelago - Clark, Roger N.; Jewett, Stephen C. (Zootaxa, 2010)
A new genus and thirteen new species of echinasterid sea stars are described from nearshore waters of the Aleutian Islands. The new genus Aleutihenricia is distinguished from Henricia by the morphology and arrangement of the skeletal ossicles. Henricia beringiana D'yakonov, 1950 is designated as the type species. The new species described include Aleutihenricia federi, Henricia lineata, H. uluudax, H. iodinea, H. rhytisma, H. gemma, H. echinata, H. vermilion, H. elachys, H. insignis, Odontohenricia aurantia, O. ahearnae, and O. violacea. In addition to the descriptions, associations between echinasterids and sponges are briefly discussed. A key to the shallow water (<20 m) Echinasteridae of the Aleutian Islands is provided.